The analysis of intestinal microflora in infants with cow's milk protein allergy - WANG Liting; ZENG Yongmei; ZHANG Jiyong; LI Weiyan; QIU Xiaoying; WANG Yuanyuan; DONG Guoqing; LIU Peihui (Guangxi Yike Daxue xuebao)
Objective To explore the changes of intestinal microflora diversity and phylum species abundance in infants with cow's milk protein allergy (CMPA), so as to provide theoretical basis for early prevention and treatment of CMPA infants. Methods Samples from 18 infants with diagnosed CMPA and 12 healthy infants were selected. Metagenomic sequencing method was used to detect intestinal microflora in feces of the two groups. Bioinformatics analysis was performed on the detection results, and the differences between the two groups were compared in terms of diversity and structure. Results The intestinal microflora Shannon index of the CMPA group was 1.232±0.367, which was significantly lower than that of the healthy control group (1.885±0.281) (P < 0.05). Overall, there were differences in phylum, genus and species between the two groups (P < 0.05). At the species level, the abundance of Bifidobacterium_longum, Bifidobacterium_bifidum, Bifidobacterium_catenulatum, Bifidobacterium_dentium, Bifidobacterium_pseudocatenulatum and other Bifidobacterium species were decreased. The breastfed CMPA infants had intestinal microflora closer to that of healthy babies. Conclusion The changes of intestinal flora may participate in the occurrence of CMPA. Such changes not only reduce the diversity of intestinal microflora, but also alter its structure. Detecting the state of intestinal microflora at an early stage and making adjustments to it according to the detection results may play a positive role in early prevention and treatment of CMPA in infants.